1960
DOI: 10.1136/bmj.2.5203.900
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcal Sepsis in Out-patients

Abstract: JOURNALIn general, in each group of those who had abnormal faecal chemical fat the faecal radioactivity determination was abnormal in about 75%, while the blood peak radioactivity was abnormal in only about 50%. On the other hand, in nearly each group, of those who had normal faecal chemical fat, nearly 80% had a normal faecal radioactivity, while the blood peak radioactivity was normal in nearly 85%.Of the two 1311 triolein determinations the faecal radioactivity determination was found to be a much better in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1961
1961
1978
1978

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Thompson et al (1960), reporting from the Middlesex Hospital, found that 82 ,', of strains isolated wvere resistant in that year as against 20% from the same hospital in 1945 (Selbie et al, 1945). Macfarlane et al (1960), dealing with out-patients attending St. Bartholomew's Hospital in 1959-60, report 39 % of staphylococci penicillinresistant compared with 6% in 1949 and 1950 (Griffiths et al, 1949(Griffiths et al, , 1950. This is very similar to the current percentage of resistant strains in out-patients attending Whipps Cross Hospital, where the figure is 33.3% (Table II).…”
Section: Discussionmentioning
confidence: 59%
“…Thompson et al (1960), reporting from the Middlesex Hospital, found that 82 ,', of strains isolated wvere resistant in that year as against 20% from the same hospital in 1945 (Selbie et al, 1945). Macfarlane et al (1960), dealing with out-patients attending St. Bartholomew's Hospital in 1959-60, report 39 % of staphylococci penicillinresistant compared with 6% in 1949 and 1950 (Griffiths et al, 1949(Griffiths et al, , 1950. This is very similar to the current percentage of resistant strains in out-patients attending Whipps Cross Hospital, where the figure is 33.3% (Table II).…”
Section: Discussionmentioning
confidence: 59%
“…[1][2][3][4][5] This study shows that the trend has continued, 81-5%' of strains now being resistant to penicillin. This result approximates to the incidence of penicillin resistance found in strains isolated from inpatients.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] This study shows that the trend has continued, 81-5%' of strains now being resistant to penicillin. This result approximates to the incidence of penicillin resistance found in strains isolated from inpatients.…”
Section: Discussionmentioning
confidence: 99%